2006
DOI: 10.1139/x06-059
|View full text |Cite
|
Sign up to set email alerts
|

Spatial analysis enhances modelling of a wide variety of traits in forest genetic trials

Abstract: Spatial analysis of progeny trial data improved predicted genetic responses by more than 10% for around 20 of the 216 variables tested, although, in general, the gains were more modest. The spatial method partitions the residual variance into an independent component and a two-dimensional spatially autocorrelated component and is fitted using REML. The largest improvements in likelihood were for height. Traits that exhibit little spatial structure (stem counts, form, and branching) did not respond as often. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
108
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 98 publications
(127 citation statements)
references
References 30 publications
18
108
1
Order By: Relevance
“…Variables recorded as counts were not transformed as it was observed that transformation using the square root for counts did not further normalize the distribution (Dutkowski et al 2006). …”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Variables recorded as counts were not transformed as it was observed that transformation using the square root for counts did not further normalize the distribution (Dutkowski et al 2006). …”
Section: Discussionmentioning
confidence: 99%
“…The large physical area needed for a progeny trial usually exhibits considerable variation in environmental conditions (Bian et al 2017;Dutkowski et al 2006;Chen et al 2017). To reduce such environmental heterogeneity, an experimental design subdividing the trial into blocks is usually used (Williams et al 2002).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations